Ex vivo accuracy of three electronic root canal length measurement devices: X-smart pro+, root ZX mini, and propex pixi - Muhammed Ayhan; Berkehan Aykanat (BMC Oral Health)
Abstract Background The X-Smart Pro+ (Dentsply Sirona) endodontic device has been recently introduced. However, to the best of our knowledge, to date, no ex vivo study evaluating the performance of the X-Smart Pro+ in detecting the apical constriction has been published in English-language journals. To address this gap in literature, our study aimed to evaluate and compare the accuracy of three electronic apex locators (EALs) (X-Smart Pro+, Root ZX mini, and Propex Pixi) in determining apical constriction ex vivo. Methods Thirty-six extracted single-rooted human maxillary lateral incisors were standardized to a root length of 17 mm. The actual working length (AWL) was determined to be 0.5 mm shorter than the major apical foramen using a #15 K-file. The teeth were then placed in an ex vivo model, and electronic measurements were performed using three different EALs. Statistical analysis was performed on the data using analysis of variance (α = 0.05). Results No significant difference was found between the tested EALs in terms of accuracy in determining the apical constriction (P > 0.05). The average distances to the AWL were measured as 0.19 ± 0.36, 0.22 ± 0.21, and − 0.06 ± 0.34 mm for X-Smart Pro+, Root ZX mini, and Propex Pixi, respectively. Conclusions Within the limitations of this ex vivo study, X-Smart Pro+, Root ZX mini, and Propex Pixi EALs demonstrated comparable accuracy in AC determination, with no statistically significant differences among the three devices.